2017
DOI: 10.1007/s13337-016-0355-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and prophylactic efficacy of herbal extracts against experimentally induced chicken infectious anaemia in chicks: assessing the viral load and cell mediated immunity

Abstract: Chicken infectious anaemia virus (CIAV) is an economically important and a highly immunosuppressive virus affecting poultry industry worldwide. In this study we assessed the immunomodulatory effects of four herbal preparations namely Withania somnifera, Tinospora cordifolia, Azadirachta indica and E Care Se Herbal in resisting the viral multiplication and immunosuppression inflicted by CIAV in chicks. Day-old chicks (n = 90) were randomly and equally divided into six groups (Groups A-F). Groups A-D were admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Natural resources of Wi-N and CAPE (Ashwagandha and honeybee propolis, respectively) have long history of use in traditional home medicine systems, are generally recognized as safe, easily available and affordable. There are several reports that provide evidence that both CAPE and Ashwagandha derived withanolides (Akyol et al, 2013;Amoros et al, 1994;Anjaly & Tiku, 2018;Cai et al, 2015;Erdemli et al, 2015;Kaul & Wadhwa, 2017;Kwon et al, 2019;Latheef et al, 2017;Lyu et al, 2005;Munagala et al, 2011;Murtaza et al, 2015;Serkedjieva et al, 1992;Zandi et al, 2011) possess antiviral activity. Mechanism of action of antiviral activities has not been completely understood.…”
Section: Mm/gbsa Free Binding Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Natural resources of Wi-N and CAPE (Ashwagandha and honeybee propolis, respectively) have long history of use in traditional home medicine systems, are generally recognized as safe, easily available and affordable. There are several reports that provide evidence that both CAPE and Ashwagandha derived withanolides (Akyol et al, 2013;Amoros et al, 1994;Anjaly & Tiku, 2018;Cai et al, 2015;Erdemli et al, 2015;Kaul & Wadhwa, 2017;Kwon et al, 2019;Latheef et al, 2017;Lyu et al, 2005;Munagala et al, 2011;Murtaza et al, 2015;Serkedjieva et al, 1992;Zandi et al, 2011) possess antiviral activity. Mechanism of action of antiviral activities has not been completely understood.…”
Section: Mm/gbsa Free Binding Energymentioning
confidence: 99%
“…Both are known to boost the immune function, possess a variety of prophylactic and therapeutic activities (Akyol et al, 2013;Anjaly & Tiku, 2018;Erdemli et al, 2015;Kaul & Wadhwa, 2017;Murtaza et al, 2015). Besides, Withaferin-A , one of the withanolides from Ashwagandha, was shown to possess inhibitory activity for HPV and influenza viruses (Cai et al, 2015;Latheef et al, 2017;Munagala et al, 2011). Several studies have also provided evidence that the honeybee propolis inhibits variety of viruses including herpes simplex virus, sindbis virus, parainfuenze-3 virus, human cytomegalovirus, dengue virus type-2, influenza virus A1 and rhinovirus (Amoros et al, 1994;Kwon et al, 2019;Lyu et al, 2005;Serkedjieva et al, 1992;Zandi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indian Ayurvedic herb, Ashwagandha (Withania sominifera) and honey bee propolis have been heavily used in traditional home medicine systems. Both of these are trusted to boost the immune function, possess a variety of prophylactic and therapeutic activities (Latheef et al, 2017;Munagala et al, 2011). Several studies have provided evidence that honeybee propolis inhibits variety of viruses including herpes simplex virus, sindbis virus, parainfuenze-3 virus, human cytomegalovirus, dengue virus type-2, influenza virus A1 and rhinovirus (Amoros et al, 1994;Kwon et al, 2019;Munagala et al, 2011;Serkedjieva et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…and Glycyrrhiza uralensis, to drinking water can enhance the immune response in immunosuppressed chickens with the reticuloendotheliosis virus [ 23 ]. Further evidence of the immunomodulatory effects of herbal extracts was provided by Latheef et al (2017) who reported that Withania somnifera , Tinospora cordifolia and Azadirachta indica were capable of inhibiting the replication of the chicken infectious anemia virus and increasing the cell-mediated response of chickens against this virus [ 22 ]. However, the immunomodulatory effects of herbal extracts have never been investigated in domestic pigeons.…”
Section: Introductionmentioning
confidence: 99%